PENDIDIKAN KARAKTER DALAM PERSPEKTIF ISLAM DAN SUMBER DAYA MANUSIA PROFESIONAL - Ahmad Zakariya (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2018)
The purpose of writing this article is to describe how character education in Islamic perspective towards Professional Human Resources. Character education in Islamic perspective is education that shapes the character and character of human excellence in terms of intellectual intelligence (IQ), emotional (EQ), and spiritual (SQ). The totality of these three intelligences will make perfect human beings (insân kâmil) or Professional Human Resources. IQ forms a rational intelligence of mind. While emotionally intelligent is the emotional mind which is an impulsive and influential system of understanding, sometimes illogical. These two thoughts work in harmony, complementarity. SQ is the spiritual intelligence that shapes the human mind into shiddiq, istiqamah, amanah, fathanah, and tabliq. The synchronization of IQ, EQ, and SQ will form a vertical relation (Hablumminallah) and a horizontal relation (Hablumminnannas) that can be used as a guide of a responsible action in the world and in the hereafter. Keywords: Character Education, IQ, EQ, SQ, Islam, Professional Human Resources.